2010
DOI: 10.1158/0008-5472.can-10-0434
|View full text |Cite
|
Sign up to set email alerts
|

Phosphomimetic Mutants of Pigment Epithelium-Derived Factor with Enhanced Antiangiogenic Activity as Potent Anticancer Agents

Abstract: Pigment epithelium-derived factor (PEDF) is an endogenous inhibitor of angiogenesis and a promising anticancer agent capable of suppressing solid tumor growth in animal cancer models. We have previously shown that PEDF can be phosphorylated and that distinct phosphorylation states of this factor differentially regulate its physiologic function. Here, we report that phosphomimetic mutants of PEDF, which possess significantly increased antiangiogenic activity, are much more efficient than wild-type (WT) PEDF in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
34
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 39 publications
5
34
2
Order By: Relevance
“…Apoptosis-According to our previous results (19), the antiproliferative effect of PEDF toward ECs was associated with an enhanced EC apoptosis. To verify this, we first compared the rate of WT-PEDF-and EEE-PEDF-induced apoptosis by TUNEL assay.…”
Section: Effect Of Wt-pedf and Eee-pedf On Endothelial Cellmentioning
confidence: 51%
See 4 more Smart Citations
“…Apoptosis-According to our previous results (19), the antiproliferative effect of PEDF toward ECs was associated with an enhanced EC apoptosis. To verify this, we first compared the rate of WT-PEDF-and EEE-PEDF-induced apoptosis by TUNEL assay.…”
Section: Effect Of Wt-pedf and Eee-pedf On Endothelial Cellmentioning
confidence: 51%
“…This effect was suggested to involve inhibition of activity and/or expression of VEGF (4, 31) as well as the proapoptotic activity of PEDF toward immature and migrating ECs (4, 31, 32). Yet, in our previous study, which employed three different xenograft models to test the anticancer effect of WT-PEDF and its mutants, these agents did not affect VEGF expression and activity in vivo, implying direct action on tumor ECs as a major determinant of the observed anticancer activity (19). Though still controversial, it has been reported that PEDF also exerts a direct antitumor effect, possibly by inducing either antiproliferative or prodifferentiation activities toward cancer cells (31,33).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations